Circular service management: toward conceptual understanding and service research priorities for a more sustainable future - Karpen Ingo Oswald; Edvardsson Bo; Tronvoll Bård; Jaakkola Elina; Conduit Jodie (Emerald Publishing, 2025)
Purpose
Service managers increasingly strive to achieve sustainability through strategies centered on circularity. With a focus on saving, extending and (re)generating resources and their enclosing service systems, circularity can contribute to environmental, social and financial gains. Yet, the notion of circularity is surprisingly understudied in service research. This article seeks to provide an initial conceptual understanding of circular service management, introducing illustrative strategies and research priorities for circular service management. This paper provides a roadmap for scholars, practitioners and policymakers to develop a deeper understanding of the opportunities from adopting circular services.
Design/methodology/approach
The authors explore the concept of circular service management by drawing upon existing literature on sustainability, circularity and service research. Strategies of circular service management and research priorities emerge on the basis of industry best practice examples and research on sustainability challenges and opportunities.
Findings
Service researchers have largely ignored the concept and role of circularity for service businesses. Extant research on the topic nearly exclusively features in non-service journals and/or does not seek to advance service theory through circularity. This article argues that circular service management enables the implementation of service thinking in the pursuit of sustainability and outlines four types of circular service management strategies.
Originality/value
The authors introduce the concept of circular service management and highlight the role of service research for designing and managing circular systems and operations. This article also offers a research agenda connecting managerial challenges and opportunities with key service research priorities for circular service management. This provides a roadmap for scholars, practitioners and policymakers to develop a deeper understanding of pursuing circular services, thereby contributing to a more sustainable future.